(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the phenomenon of at-tanazu’ (التنازع ) in the Arabic language, that is, the problem of two verbs striving for superiority in controlling one noun. The study covers the main forms of tanazu’ - possessive, complement and mixed cases based on examples. Also, the difference in views between the Basra and Kufa schools of grammar, their narrative and intellectual arguments are analyzed comparatively. The article reveals the theoretical and practical significance of the approaches of both schools. The results of the study are important for a deeper understanding of the syntax of the Arabic language and the correct application of the phenomenon of tanazu’.